Developing a Mental Health Measurement Strategy to Capture Psychological Problems among Lower Caste Adolescent Girls in Rural, South India. (February 2019) - Mazzuca, April; Nagarchi, Dawood; Ramanaik, Satyanarayana; Raghavendra, T; Javalkar, Prakash; Rotti, Sarojini; Bhattacharjee, Parinita; Isac, Shajy; Cohen, Alex; Beattie, Tara
Adolescent girls vulnerable to early marriage and school dropout in rural India may be at elevated risk of psychosocial problems. However, few screening instruments have been culturally adapted and validated to measure this risk. This paper describes the process by which the Primary Health Questionnaire PHQ-9, a screening instrument for depression, was tested for cultural validity as part of the Samata evaluation – an intervention to support low caste adolescent girls in rural south India to attend and complete secondary school and to delay marriage until adulthood. Three focus groups discussions (FGDs) were held with 20 adolescent girls and six outreach workers of the Samata programme in rural north Karnataka, south India. The FGDs were used to explore local expressions of psychosocial problems and to understand the acceptability and appropriateness of PHQ-9 items. A thematic content analysis was conducted on the transcripts of the FGDs. Descriptions of local expressions of psychosocial problems generally matched the items on the PHQ-9. However, not all representations of psychological symptoms were captured by this tool. Persistent worry, loneliness and isolation, and externalised behaviours were also described by participants as common expressions of psychosocial distress. Based on the limitations of translation methods, local stakeholders must be involved in evaluating the cultural appropriateness of mental health screening tools. The current research demonstrates a strategy by which to assess the cultural validity of Western psychiatric instruments with key stakeholders in low- and middle-income settings.